Salt Sales Prediction Using the Moving Average Method (A Case Study of Madura-Indonesia Salt) - Syakur, Muhammad Ali; Negara, Yudha Dwi Putra; Rachmad, Aeri; Rochman, Eka Mala Sari (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
Forecasting is a term used to forecast or predict the business that we run to see the direction in the future which uses historical data as the main reference. An appropriate strategy is needed to manage the production of salt raw materials properly, namely through sales forecasting. PT Budiono Madura Bangun Persada is a company engaged in salt processing with the brands